The elephant and the dragon : the rise of India and China and what it means for all of us - Meredith, Robyn (New York: W.W. Norton, 2008)
The Elephant and the Dragon is the essential guide to understanding how India and China are reshaping our world. With labor now unbound from geographic borders, we're seeing startling shifts in how--and where--nearly everything we buy is made. In a compelling mix of history and on-the-ground reporting, veteran journalist Robyn Meredith untangles the complex web of business and politics, as well as environmental and cultural issues that entwine India, China, and the West. She also outlines how Americans--business leaders, workers, politicians, even parents--can understand the vast changes coming and thrive in this new age.--From publisher description.
Introduction: tectonic economics -- Where Mao meets the middle class -- From the spinning wheel to the fiber-optic wire -- Made by America in China -- The Internet's spice route -- The disassembly line -- India's cultural revolution -- Revolution by dinner party -- Geopolitics mixed with oil and water -- A catalyst for competitiveness.
"With a new afterword"--Cover.
Includes bibliographical references (p. 219-236) and index.
Keywords: Globalization; India -- -- Foreign economic relations; China -- -- Economic conditions -- -- 2000-; India -- -- Economic conditions -- -- 21st century; China -- -- Foreign economic relations; United States -- -- Economic conditions -- -- 21st century; United States -- -- Foreign economic relations